Razvojne usmeritve podjetja Salonit Anhovo, d.d. - Ljubič-Mlakar, Tanja (Kovine zlitine tehnologije, 1999)
The main scope of this article is to present the main development projects of the company Salonit Anhovo, d.d. in the field of cement industry and its further development directions. In the introducing part also the production program of cements and hydraulic binders, as well as the quality assurance system are represented.
Keywords: Salonit Anhovo; cementi; projekti; razvoj; kontrola kvalitete